The Influence of School Leadership Style and Teacher’s Motivation toward Teacher’s Performance - Firman, Firman; Fitria, Happy; Rohana, Rohana (Journal of Social Work and Science Education, 2021)
The purpose of this study investigated 1) the impact of the Principal's leadership style on results, 2) the effect of motivating teachers on performance, and 3) the effect of the Principal's leadership style and motivation on performance. This research is based on quantitative approaches. The population used all teachers in SMAN 1 and SMKN 1 Rambutan, Banyuasin Regency, South Sumatra Province as samples. Since the research population has only 77 populations and all of them are sampled. Data was analyzed using a simple linear regression formula and multiple linear regression From the results of the study, it can be concluded that (1) the influence of the principal's leadership style on the performance of the SMA-SMK Negeri in the Rambutan Banyuasin district, (2) the influence of the motivation of the teacher on the performance of the SMA-SMK Negeri in the Rambutan Banyuasin district, and (3) the influence of the leadership style of the principal and the motivation of the teacher together.